Toleransi Antarumat Beragama Pada Channel YouTube Curhat Bang Denny Sumargo Episode Ustaz Khalid Basalamah - Abdul Raafi (Sekolah Tinggi Agama Islam As-Sunnah, 2025)
This research aims to identify forms of interfaith tolerance found in the content of Denny Sumargo's YouTube podcast featuring Ustaz Khalid Basalamah as the guest speaker. This study employs a content analysis method with a primary data source being the podcast video titled “TUHAN, AGAMA & KEYAKINAN!! TUHAN CUMAN SATU, KENAPA AGAMA BISA BERBEDA!?” The research method used is content analysis with coding sheets. The findings indicate that the podcast video on Denny Sumargo's YouTube channel contains various forms of interfaith tolerance. The results reveal that 40% of the statements are related to the attitude of tolerance by not forcing others to convert to Islam, 15% of the statements are related to tolerance by not insulting other religions, 30% of the statements are related to tolerance by giving freedom of worship, 15% of the statements are related to tolerance by socializing regardless of religious background, and 0% of the statements are related to mutual help among followers of different religions.